Efforts to Improve the Performance of Two-Wheeled Patrol Activities to Prevent the Occurrence of Criminal Acts of Theft at the Gresik Police - Prasetya, Bisma Adista (Police Studies Review, 2024)
The recurring issue in the jurisdiction of Polres Gresik, which increases every year, is motor vehicle theft (curanmor). Therefore, this research aims to examine the correlation between resources and methods utilized by the Satuan Samapta patrol unit, as well as prevention efforts aimed at reducing curanmor crimes within the jurisdiction of Polres Gresik. This research is conducted using a qualitative approach by collecting primary and secondary data sources through interviews, observations, and document studies on the motorcycle patrol unit of the Satuan Samapta of Polres Gresik. Subsequently, an analysis is performed using the POAC management theory (Planning, Organizing, Actuating, and Controlling) and the 6M Management theory, based on the concepts of efforts, patrols, and curanmor. From the findings of this research, based on the theories employed, the Satuan Samapta patrol unit still lacks personnel in carrying out its duties effectively. There are still many members who do not conduct patrols according to the designated routes, and evaluations are only carried out formally without proper evaluation stages by the patrol leaders. Additionally, personnel checks, vehicle inspections, and patrol administration such as Mutation Books are not implemented.